Diet-Induced Obesity Does Not Alter Tigecycline Treatment Efficacy in Murine Lyme Disease - Pětrošová, Helena; Eshghi, Azad; Anjum, Zoha; Zlotnikov, Nataliya; Cameron, Caroline E.; Moriarty, Tara J. (Frontiers in Microbiology, 2017)
Obese individuals more frequently suffer from infections, as a result of increased susceptibility to a number of bacterial pathogens. Furthermore, obesity can alter antibiotic treatment efficacy due to changes in drug pharmacokinetics which can result in under-dosing. However, studies on the treatment of bacterial infections in the context of obesity are scarce. To address this research gap, we assessed efficacy of antibiotic treatment in diet-induced obese mice infected with the Lyme disease pathogen, Borrelia burgdorferi. Diet-induced obese C3H/HeN mice and normal-weight controls were infected with B. burgdorferi, and treated during the acute phase of infection with two doses of tigecycline, adjusted to the weights of diet-induced obese and normal-weight mice. Antibiotic treatment efficacy was assessed 1 month after the treatment by cultivating bacteria from tissues, measuring severity of Lyme carditis, and quantifying bacterial DNA clearance in ten tissues. In addition, B. burgdorferi-specific IgG production was monitored throughout the experiment. Tigecycline treatment was ineffective in reducing B. burgdorferi DNA copies in brain. However, diet-induced obesity did not affect antibiotic-dependent bacterial DNA clearance in any tissues, regardless of the tigecycline dose used for treatment. Production of B. burgdorferi-specific IgGs was delayed and attenuated in mock-treated diet-induced obese mice compared to mock-treated normal-weight animals, but did not differ among experimental groups following antibiotic treatment. No carditis or cultivatable B. burgdorferi were detected in any antibiotic-treated group. In conclusion, obesity was associated with attenuated and delayed humoral immune responses to B. burgdorferi, but did not affect efficacy of antibiotic treatment.